Spastic Lower Paraparesis Due To Multiple Ossification of The Ligamentum Flavum of Fusion and Tuberous Type In The Thoracolumbar Region In A 42-Year-Old Woman - Gregorius Septayudha Suryonegoro; Frisca Angreni (International Journal of Health and Pharmaceutical (IJHP), 2025)
Ossification of the ligamentum flavum (OLF) is characterized by the replacement of ligamentum flavum tissue with mature laminar bone accompanied by hypertrophy. Although rare, its highest prevalence is reported among East Asian populations, predominantly affecting males under 50 years old, and most commonly found in the lower thoracic region. Clinically, OLF presents as a slowly progressive myelopathy, yet its precise pathogenesis remains unclear. Diagnostic imaging modalities include radiography, computed tomography (CT), and magnetic resonance imaging (MRI). This case report describes a 42-year-old female diagnosed with thoracolumbar OLF based on MRI examination. The patient presented with spastic paraparesis and hypoesthesia from both feet to dermatomes Th10–11 following a history of trauma. Lumbar radiography showed only lumbal spondylosis, while thoracolumbar MRI revealed nodular thickening of the ligamentum flavum from Th6–7 to Th12–L1, resulting in spinal canal stenosis and compression of the spinal cord. Additional degenerative findings included superior endplate degeneration of L4 and multiple intervertebral disc bulging. Neurological deficits indicated myelopathy and radiculopathy due to compression of the lateral corticospinal and spinothalamic tracts. The absence of spinal cord edema on MRI suggested a chronic onset. OLF frequently coexists with vertebral degenerative abnormalities, as observed in this patient. Based on the radiologic characteristics, the lesion represented several morphological types including extended, enlarged, fused, and tuberous forms. Laminectomy performed in this case resulted in gradual neurological recovery. In conclusion, OLF is a rare but important cause of progressive thoracic myelopathy that may lead to irreversible neurological impairment. MRI evaluation plays a crucial role in preoperative assessment of spinal canal stenosis and spinal cord compression.